CAD and fabrication of low-pass filter / Norazam Mohd Amin - Mohd Amin, Norazam (2004)
The purpose of this project is to design, simulate, fabricate and measure the characteristics of a microstrip low-pass filter operating at microwave frequencies using computer-aided design (CAD) package. A maximally flat low-pass filter with cutoff frequency of 3 GHz was designed to have an insertion loss not exceeding ldB in the passband and an insertion loss of more than 15dB in the stop band.The microstrip laminates used are 'Duroid /Rogers 5872' with a 0.5mm substrate thickness and relative permittivity (Sr) of 2.33. The filter was designed, simulated and optimized with the aid of a CAD package HP-Eesof and Genesys V8 with different typ of network. In Libra, the type of network used for the filter is 7t-network while T-network type is used in Genesys. The responses in simulation and experiment from both software are compared and found that the simulation responses from both software gave similar results but Genesys gave better responses than Libra in experimental results. The circuits from both software were fabricated at UKM Fabrication Department. The filters characteristics were determined using a Wiltron 562 Vector Network Analyser.